Characterization of drought stress-mitigating Rhizobium from faba bean (Vicia faba L.) in the Chinese Qinghai-Tibet Plateau - Li, Ping; Teng, Changcai; Zhang, Jinfa; Liu, Yujiao; Wu, Xuexia; He, Tao (Frontiers in Microbiology, 2023)
Rhizobium-driven symbiotic nitrogen-fixation in legumes not only benefits the growth but also enhances the stress tolerance of plants. Isolating and characterizing efficient, drought-tolerant rhizobia is a central goal for improving crop yields in arid regions.Here, we phylogenetically and biochemically characterized a novel strain of Rhizobium ('QHCD11') sampled from the root nodules of faba beans growing in an arid agricultural area in Qinghai-Tibet. We further tested the drought tolerance of the strain as well as of 'Qingcan 14' faba bean seedlings inoculated with it. Biochemical characterization involved bromothymol blue (BTB) tests, carbon metabolic profiling (Biolog GENIII), DNA-DNA hybridization (dDDH) assays, average nucleotide identity (ANI) analyses, and 16S rRNA sequencing. The result indicated that strain 'QHCD11' likely belongs to the Rhizobium indicum species. Drought stress tolerance was assessed by exposure to polyethylene glycol (PEG-6000) at concentrations of 0%, 10%, 15%, and 20%. Increasing concentrations of PEG-6000 tended to result in decreased growth of 'QHCD11', although the strain performed better at 20% PEG 6000 than at 15%. Inoculation of drought-stressed faba bean seedlings with strain 'QHCD11' improved root vitality, chlorophyll content, antioxidant enzyme activities, and plant height. We suggest that inoculation of faba beans with 'QHCD11' is an environmentally sound strategy for mitigating crop drought stress in arid and semi-arid regions. In addition, the results presents here will benefit future studies into faba bean-rhizobia symbioses under drought stress.